Влијание на депресивноста врз квалитетот на живот кај жени лекувани од рак на дојка - Ристевска Димитровска, Гордана (Медицински факултет, УКИМ, Скопје, 2016)
In Macedonia there are very few epidemiological data on the prevalence of depressive disorder in women treated for breast cancer and the impact of depression on their quality of life. The objectives of this study are to investigate the prevalence of depressive disorder and to determine and quantify the relationship of depressive disorder with psychosocial factors in women treated for breast cancer, and to investigate the impact of depression on quality of life in women treated for breast cancer. The study has prospective design and was conducted in the oncology ward at Clinical Hospital "Dr. Trifun Panovski" in Bitola, and University Clinic for Radiotherapy and Oncology in Skopje in the period from January 2014 to July 2015. This study included 218 female patients treated for breast cancer, older than 18 years, who were treated with different clinical methods and are in a different time point from the initial cancer treatment. The study group was comprised of 113 patients, treated for breast cancer, who have clinically significant depression at study entry. The control group was comprised of 105 patients, treated for breast cancer without clinically significant depression at study entry. All respondents were interviewed twice, once initially and a second time after a period of 6 months, in terms of socio-demographic, psychosocial and oncological parameters. The levels of depression, resilience and quality of life were also measured during both interviews. The prevalence of depressive symptoms in women treated for breast cancer is high, initially, 51.8% of patients had clinically significant depression and 16.1% had major depression. After 6 months, the depressive symptoms are reduced, clinically significant depression was observed in 30%, and major depression in 8.2%. In our group, significant predictive factors for the occurrence of depression are: lower levels of education, sedentary lifestyle and fear of cancer relapse. Patients initially rated cognitive and role functioning as best; fatigue was the most disabling symptom and financial difficulties have significant negative impact on their quality of life. After a period of 6 months, patients with breast cancer had significantly improved quality of life in multiple domains. Depression had statistically and clinically significant, negative impact on all aspects of quality of life of women treated for breast cancer, and more severe depression reduces quality of life significantly more. More resilient patients have a significantly better quality of life, while the worse socio-economic status negatively affects multiple domains of quality of life. Psychosocial care for patients with breast cancer and their families should be recognized as a necessary component in daily clinical practice, because of the significant influence of psychosocial factors on the quality of life of patients through all stages of the disease.
Докторска дисертација одбранета во 2016 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Бети Дејанова.